Conflict of Interest by Director Which Also Act as Liquidator for Company Liquidation Process - Gaffar, Arif (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This article delves into the complexities surrounding conflicts of interest faced by directors involved in company liquidation processes. Furthermore, the article also examines the legal and ethical dimensions of such conflicts, considering the director's fiduciary duties and responsibilities to act in the best interests of the company, shareholders, and creditors. Conflicts may arise when directors have personal interests or relationships that diverge from their duty to prioritize the company's welfare. The abstract underscores the significance of transparency, disclosure, and adherence to corporate governance principles in navigating these conflicts effectively. Through an analysis of relevant regulation frameworks, this article examines insights into identifying conflicts of interest within the Company, especially when the Director are appointed as the liquidator.